Postnephrectomy arteriovenous fistula - Baptista-Silva, José Carlos Costa; Figueiredo, Luiz Francisco Poli de; Castro, Marcos Joaquim; Veríssimo, Marcos José Martins; Camara, André Luiz Guimarães (São Paulo Medical Journal, 1997)
The development of the postnephrectomy arteriovenous fistula (PNAVF) between the renal vessels stumps is rare. Here we present a case report of PNAVF, and review the diagnosis, treatment and prevention.The most common clinical features include a loud murmur over the previous nephrectomy scar, and heart failure resistant to common medical treatment. A 58-year-old white woman was admitted to the hospital for a complete evaluation of an unexplained congestive heart failure with no response to common medical treatment. She had had a right nephrectomy for pyonephrosis 13 years before. The diagnosis of PNAVF was suspected because over the right lumbar region a definite trill was palpated, and on auscultation a harsh, machinery-like murmur was heard.The diagnosis was confirmed by aortogram and selective renal arteriography. In May 1989, the right arteriovenous was excised through a right subcostal transperitoneal approach. The renal vessel stumps were individually ligated and sutured separately close to aorta and vena cava. The patient’s postoperative course was entirely uneventful in the following seven years. We conclude that during nephrectomy, the renal vessels should be ligated separately, and the transfixation in mass of the stumps avoided to prevent arteriovenous fistula.